Sociodemographic and clinical characteristics of 380 cases of odontogenic lesions in a Brazilian population - Silva, Noemi Martins Gomes da; Silva, Maria Vitória Zeno Passos da; Vinhandelli, Guilherme Santos; Barroso, Danielle Resende Camisasca; Barros, Liliana Pimenta de; Silva, Daniela Nascimento; Vaz, Sérgio Lins de Azevedo; Henriques, Águida Cristina Gomes (Journal of Oral Diagnosis, 2025)
Objective: Describe the sociodemographic and clinical characteristics related to odontogenic cysts and tumors in a population from the state of Espírito Santo, Brazil. Methods: All cases of odontogenic cysts and tumors diagnosed at the Oral Pathological Anatomy Service (SAP) of the Universidade Federal do Espírito Santo (UFES) between 2004 and 2022 were selected. The lesions were categorized according to the 2022 WHO classification. The frequency of cysts and tumors was calculated and the following information was collected: age, sex and skin color of the patients, presence of signs and symptoms, and specific lesion data such as radiographic appearance, location, size, association with unerupted teeth, tooth displacement and root resorption, whether the lesion corresponds to a recurrence, and treatment modality. Results: Cysts were more frequent than odontogenic tumors, especially radicular cysts. Ameloblastomas and cemento-ossifying fibroma were the most common odontogenic tumors. Conclusion: This study contributes to a better understanding and differentiation of odontogenic lesions, supporting dentists in the diagnostic process and treatment of these pathologies.